Biaxial fatigue limits and crack directions for stainless steel specimens with circular holes. (1st April 2017) - Chaves, V.; Beretta, G.; Navarro, A.
Abstract: High cycle fatigue tests have been conducted for stainless steel AISI 304L. The geometry is a thin-walled tube with a passing-through hole. The tests are axial, torsional and in-phase axial-torsional, all of them under load control with R = - 1 . From the tests, the S-N curves are constructed and the fatigue limits are calculated. The crack surface is analyzed, with especial attention to the first 500 μm. The crack has begun close to the point of maximum principal stress at the hole surface and has followed, approximately, the maximum principal stress direction.